Rancang Bangun Aplikasi Tahfidz dengan Metode Rapid Application Development - Fauza Ibrahim Farid; Alon Jala Tirta Segara (Fakultas Ilmu Komputer, Universitas Dian Nuswantoro, 2025)
The conventional system for tracking Qur'an memorization at SMPIT Salman Alfarisi Boarding School poses significant challenges, including scattered data, inconsistent record-keeping, and difficulties in reporting. A preliminary study found that 64% of supervisors consider this manual system ineffective. This research aims to address these issues by developing an Android-based application for tracking tahfidz, utilizing the Rapid Application Development (RAD) methodology. The development process involved identifying user requirements through observation, interviews, and a literature review, followed by system design using UML and interface mockups. The system was implemented using Flutter for the mobile application and Laravel for the REST API. Evaluation was conducted through questionnaires and black-box testing. The results demonstrate that the application enhances the effectiveness of record-keeping and simplifies data access, with user evaluations confirming the system's practicality and utility. All nine functional test cases yielded a